Diet of two coastal nototheniid fish from Terra Nova Bay, Ross Sea - Vacchi, M.; Mesa, M. La; Castelli, A. (Antarctic Science, 1994)
An investigation into the feeding habits of two demersal nototheniids, Trematomus bernacchii and T. centronotus , showed that the most important prey were polychaetes, molluscs and euphausiids for T. bernacchii and polychaetes and amphipods for T. centronotus. Epifaunal (e.g. Barrukia cristata ) and tube-dwelling polychaetes ( Amphicteis cfr. midas and Amythas membranifera ) were common in the diet of both species. Bivalvia including Adamussium colbecki were found in the diet of T. bernacchii. Epifaunal gastropods (Trochidae) were an occasional prey for T. centronotus. Amphipods (mainly Acanthonotozomatidae) and the euphausiid Euphausia frigida were the main crustacean food of T. centronotus and T. bernacchii respectively. Our data suggest a difference in the feeding behaviour of the two nototheniid species, although both appear capable of feeding on common epibenthic invertebrates.